Enlarging bullae and spontaneous pneumothorax associated with CPAP use: A case series of three patients - Allison Navarrete-Welton; Kamran Manzoor; Taro Minami; Naomi Kramer (Journal of Mechanical Ventilation, 2024)
Objectives Spontaneous pneumothorax among patients with obstructive sleep apnea treated by nocturnal continuous positive airway pressure (CPAP) has not been well documented. Methods We present three cases of patients on chronic CPAP who experienced spontaneous pneumothorax without clear predisposing factors. Their personal and family medical histories, imaging characteristics, and CPAP settings are reviewed. Results In all three cases, the patients had bullae ipsilateral to the pneumothoraces that either formed (n = 1) or grew significantly (n = 2) after CPAP initiation. No other risk factors for pneumothorax or bullae were identified. Conclusions This case series demonstrates a need for further investigation into a possible connection between spontaneous pneumothorax, bullae development, and CPAP use.